KONSTITUSIONALITAS PENGATURAN BATAS USIA CALON WAKIL PRESIDEN - Jessica Carolina Jaya; Rorry Pramudya; Yuli Fitriah (The Juris, 2026)
This research examines the legal dynamics and constitutional implications of age requirements for vice-presidential candidates in Indonesia. The study focuses on two main legal aspects: the original legal reasoning (ratio legis) of the age limit and the shift in judicial interpretation following the Constitutional Court's landmark ruling. The findings indicate that while the original age limit aimed to ensure leadership stability, the Constitutional Court's decision has shifted the paradigm toward acknowledging the political experience of the younger generation. However, this shift has raised critical concerns regarding legal certainty and the boundaries of judicial authority.